GABPA protects against gastric cancer deterioration via negatively regulating GPX1: GABPA is an anti-cancer gene in gastric cancer progression - Yin, Binghua; Dong, Bing; Guo, Xiaohui; Wang, Can; Huo, Huazhi (Journal of Medical Biochemistry, 2022)
Background: To explore the anti-cancer role of GABPA in the progression of gastric cancer (GC), and the underlying mechanism.Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to detect the expression pattern of GABPA in 45 pairs of GC and non-tumoral tissues. The relationship between GABPA expression and clinicopathological indicators of GC patients was analyzed. In AGS and SGC-7901 cells overexpressing GABPA, their migratory ability was determined by transwell and wound healing assay. The interaction between GABPA and its downstream target GPX1 was explored by dual-luciferase reporter assay, and their synergistical regulation on GC cell migration was finally elucidated.Results: GABPA was downregulated in GC tissues in comparison to normal ones. Low level of GABPA predicted high incidences of lymphatic and distant metastasis in GC. Overexpression of GABPA blocked AGS and SGC-7901 cells to migrate. GABPA could target GPX1 via the predicted binding site. GPX1 was upregulated in clinical samples of GC, and negatively correlated to GABPA level. The anti-cancer effect of GABPA on GC relied on the involvement of GPX1. Conclusions: GABPA is downregulated in GC samples, which can be utilized to predict GC metastasis. Serving as a tumor suppressor, GABPA blocks GC cells to migrate by targeting GPX1.
Keywords: GABPA; GPX1; Gastric cancer; Migration